Comment on Variational Iteration Method for q-Difference Equations of Second Order. (10th July 2012) - Wu, Guo-Cheng
Abstract : Recently, Liu extended He's variational iteration method to strongly nonlinear q -difference equations. In this study, the iteration formula and the Lagrange multiplier are given in a more accurate way. The q -oscillation equation of second order is approximately solved to show the new Lagrange multiplier's validness.